Prevalence and Mortality of Heart Failure Stages in a Free‐Living Older Adult Population: Data From the Brazilian Longitudinal Study of Adult Health - Altair I. Heidemann; Angela B. S. Santos; Marcio S. Bittencourt; Antonio L. P. Ribeiro; Luis E. Rohde; Paulo A. Lotufo; Bruce B. Duncan; Murilo Foppa (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Heart failure (HF) has a major impact on public health. HF staging helps capture preclinical disease and its progression to advanced stages. There are scarce data on HF staging from longitudinal studies in Latin America. This study aimed to determine the prevalence and mortality of HF stages in a Brazilian adult cohort of participants 60 years old and over. Methods The ELSA‐Brasil (Brazilian Longitudinal Study of Adult Health) multicentric cohort comprises 15 105 adults. From 2008 to 2010, ELSA carried out interviews and clinical, laboratory, and cardiovascular tests. In this analysis, we included participants 60 years old and over who had an echocardiogram performed at baseline visit and additional information regarding risk factors and functional capacity. Results There were 2356 participants (65±4 years; 53% women) with baseline echocardiogram. Of these, 504 (21%) participants were considered at low risk for developing HF (stage 0). Prevalence of HF was 1026 (44%) for stage A (at risk for HF), 557 (24%) for stage B (pre‐HF), and 269 (11%) for stage C (symptomatic HF), with different distribution between sexes (P<0.001). Multivariable risk‐adjusted model for all‐cause mortality over a median follow‐up of 12 years, found 6%, 12%, 18%, and 27% for stages 0, A, B, and C, respectively, with hazard ratios of 1.82 [95% CI, 1.2–2.7], 2.52 [95% CI, 1.7–3.8], and 4.29 [95% CI, 2.8–6.6], using as reference stage 0. Conclusions The high prevalence of symptomatic, and preclinical HF in older adults and the increased mortality with disease progression may be responsible for an elevated public health burden. This information is critical for understanding and planning health policies for older adults in middle‐income countries.